Developing a potential business model for the automotive and the energy industry - Holger Benad; Martin Bode; Andreas Hack; Peter Kleine-Möllhoff; Hanna Wagner (Hochschule Reutlingen, ESB Business School, 2013)
This paper aims to present a sustainable business model for eMobility. In order to achieve this goal four different working packages are created. First of all different types of innovation are studied and defined focusing on disruptive innovations. Next different definitions of business models are analyzed and a modified business model is designed which includes eight main components - strategy, value proposition, financial aspects, resources, processes, environment, networks & channels as well as customer & market scope. In the following part the company Hilti, a supplier of the construction industry is researched and analyzed regarding its business model and the possible disruptive innovation fleet management. Then based on previous analyses a business model for eMobility is developed. The proposed business model aims at propagating eMobility, making effective advertising and testing different technologies in the field. Therefore the paper is introducing a business model for a taxi company and defining each component in detail. It presents potentials of eMobility in general and facts about the taxi industry to generate a better view of the overall situation. The paper closes with an outlook on further potentials of the proposed business model.
Keywords: 650